Flea-borne Rickettsia species in fleas, Caldas department, Colombia - Carol B Colonia; Alejandro Ramírez-Hernández; Juliana Gil-Mora; Juan C Agudelo; Gabriel Jaime Castaño Villa; Camilo Pino; Paola Betancourt-Ruiz; Jorge E Pérez Cárdenas; Lucas S Blanton; Marylin Hidalgo (Journal of Infection in Developing Countries)
Introduction: Rickettsioses are zoonotic diseases caused by pathogenic bacteria of the genus Rickettsia and transmitted to man by means of arthropod vectors such as ticks, fleas, mites and lice. Historically, Caldas Department has reported a significant number of cases of murine typhus to the Colombian national health surveillance system, and consequent studies of flea-borne rickettsiosis identified the circulation of Rickettsia typhi and Rickettsia felis in multiple municipalities. Our aim was to genotype species of Rickettsia detected in fleas collected from domestic and wild mammals in Caldas.